Analisis Akad Salam pada Transaksi Jual Beli Melalui E-Commerce - Rozalina Mirwan; Titin Suprihatin; Nandang Ihwanudin (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze buying and selling transactions in e-commerce, particularly on Shopee, from the perspective of Islamic economics. Using a descriptive method with a qualitative approach, this research evaluates the operational mechanisms of e-commerce transactions and their compliance with the principles of the salam contract. The findings indicate that transactions with upfront cash payments meet the criteria of the salam contract in accordance with Sharia requirements. However, potential irregularities in transactions were identified and addressed through Shopee's protection system, which allows buyers to exercise their khiyar rights based on the type of irregularity. This protection ensures fairness, convenience, and security for buyers in online transactions, even though the products cannot be directly inspected. Trustworthiness (amanah) is a crucial element in building buyer confidence. It involves transparently conveying product information, providing detailed descriptions of product conditions, and using media that accurately represent the actual condition of the products. The seller's consistency in maintaining trustworthiness in accordance with the salam contract can enhance buyer trust and loyalty. In conclusion, e-commerce transactions can align with Islamic economic principles if conducted in compliance with Sharia guidelines, particularly the salam contract, and supported by trustworthiness. Further research is recommended to explore the implementation of Sharia principles in transactions involving other payment methods, such as COD and credit/installments.